Workers Versus Austerity: The Origins of Ontario’s 1995-1998 ‘Days of Action’ - Kellogg, Paul (Socialist Studies / Études socialistes, 2011)
The Great Recession has left in its wake an expected “age of austerity” where deficits accumulated to stave off economic collapse, are being addressed through steep cuts to government spending, with profound implications for social services and public sector employment. In an earlier era of austerity, eleven mass strikes and enormous demonstrations swept through the major cities of Ontario. This Days of Action movement – which has real relevance for the current period – began in the fall of 1995, continued through all of 1996 and 1997, and came to an end in 1998. This article, part of a larger research project, focuses on the movement’s origins. Two themes shape the overall project: the relation between social movements “outside” the workplace and union struggles themselves; and the relationship between the energetic inexperience of newly‐active union members, and the pessimistic institutional experience embodied in a quite developed layer of full‐time union officials. It is the former – the dialectic between social movements and trade unions in the Days of Action, that will be the focus of this article.